Bacillus Cereus catheter related bloodstream infection in a patient in a patient with acute lymphblastic leukemia - Lütfiye Öksüz; N Gurler; M Muftuoglu; FD Sargin; SK Besisik (Mediterranean Journal of Hematology and Infectious Diseases)
Bacillus cereus infection is rarely associated with actual infection and for this reason single positive blood culture is usually regarded as contamination . However it may cause a number of infections, such catheter-related blood stream infections. Significant catheter-related bloodstream infections (CRBSI) caused by Bacillus spp. are mainly due to B.cereus and have been predominantly reported in immunocompromised hosts1 . Catheter removal is generally advised for management of infection. In this report, catheter-related bacteremia caused by B.cereus in a patient with acute lymphoblastıc leukemia (ALL) in Istanbul Medical Faculty was presented.A 44-year old man presented with fatigue, weight loss, epistaxis and high fever. A double-lumen Hickman–catheter (Bard 12.0 Fr, Round Dual Lumen) was inserted by surgical cut-down to access the right subclavian vein which would be necessary for allogeneic stem cell transplantation. Three weeks later the patient presented with high fever and headache. Bacillus spp. was isolated from the cathether while blood culture obtained from the peripheral vein remained negative. The bacterial identification was confirmed as B.cereus using VITEK identification system